Young Croatian Language Learners - Mihaljević-Djigunović, Jelena (Array, 2008)
The chapter gives a review of the early FL learning field in Croatia. Following an overview of the Croatian FL education context, the author analyses characteristics of the Croatian approach to teaching young learners. In particular she focuses on learner-centredness, the teacher’ s role, functional approach to teaching grammar, and learner strategies. These are illustrated with YL classroom examples from a national early FL learning project.